Till Geography Do Us Part? Prolegomena to an Economic and Monetary Union between the Dominican Republic and Haiti - Moreira, Emmanuel Pinto (2012)
This paper offers a preliminary assessment of the potential benefits and costs of an economic and monetary union (EMU) between the Dominican Republic and Haiti -- two countries sharing the same island but whose history is one of conflict and divergent economic prospects in recent decades. After a brief review of the historical context, it examines the nature of these potential benefits and costs. It then conducts a preliminary analysis (using basic statistical techniques) of some key criteria for the formation of an economic and monetary union between the two countries. A more formal analysis of business cycle synchronization, based on basic and extended integrated vector auto-regression models with exogenous variables (VARX), is developed next. Overall, the analysis suggests that at this stage several economic criteria are not satisfied for the two countries to fully benefit from an economic and monetary union. At the same time, however, the endogeneity of most of these criteria (including the degree of business cycle synchronization) militates in favor of an aggressive medium-term agenda for integration between them.